2012
DOI: 10.1901/jaba.2012.45-315
|View full text |Cite
|
Sign up to set email alerts
|

A Computer‐based Program to Teach Braille Reading to Sighted Individuals

Abstract: Instructors of the visually impaired need efficient braille-training methods. This study conducted a preliminary evaluation of a computer-based program intended to teach the relation between braille characters and English letters using a matching-to-sample format with 4 sighted college students. Each participant mastered matching visual depictions of the braille alphabet to their printed-word counterparts. Further, each participant increased the number of words they read in a braille passage following this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
(30 reference statements)
3
23
0
1
Order By: Relevance
“…The current study extended the results of Scheithauer and Tiger (2012) findings that suggest the utility of this computer-based instructional program.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The current study extended the results of Scheithauer and Tiger (2012) findings that suggest the utility of this computer-based instructional program.…”
Section: Discussionsupporting
confidence: 77%
“…First, similar to the results of Scheithauer and Tiger (2012), participants in the current study completed the training program quickly and successfully identified all braille characters with near perfect accuracy after instruction. Although computer training taught only the skill of matching braille characters to text letters, the emergence of rudimentary braille reading was also noted, with a mean of 26 words read during the posttest assessment across both groups.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Teachers who teach Braille to the students require training. A variety of teacher training programmes are conducted at various institutes to make the teachers proficient in Braille [6]. This paper suggests a solution that does not involve training, for teachers who are involved solely in the evaluation of answers written in Braille, and also for parents of visually impaired children, who are not well-versed with Braille.…”
Section: Introductionmentioning
confidence: 99%